EXPLORING THE PSYCHOLOGICAL AND METHODOLOGICAL FOUNDATIONS OF LANGUAGE EDUCATION - Yoʻldosheva Farangiz Ravshanbek qizi; Normatova Yulduz Nurnazarovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: this article is dedicated to the field of language education, focusing primarily on effective methods used in language learning, as well as interactive techniques, their significance, along with drawbacks. Additionally, the article discusses the phychological foundations of language learning, together with its phychology